Pemanfaatan Digitalisasi sebagai Penguatan Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia pada Era Society 5.0 - Wachidah, Liana Rochmatul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Digital media in the era of society 5.0 is the result of the evolution of information and communication technology which has had a significant impact on various aspects of people's lives. One of them influences aspects of education, especially learning Indonesian and character building of students. The aim of this research is to describe the use of digitalization as strengthening character education in Indonesian language learning in the era of society 5.0. This research uses qualitative research with a descriptive approach and is supported by literature study. The data source in this research is that the researcher acts as the key instrument and the data for this research is in the form of observations and literature studies. Data collection techniques involve searching library sources such as books, journals, notes and reports that are relevant to the topic or issue being discussed. The data analysis technique for this research is through data grouping, presentation, verification and conclusions. The results of this research are strengthening character in learning Indonesian by utilizing digitalization through applications, learning platforms and learning websites. Digitalization through Indonesian language learning websites has two systems. First, web-based learning for students has seven features: (1) home; (2) lessons; (3) training; (4) tasks; (5) report, (6) edit profile; and (7) guidance. Second, web-based learning for teachers has six features, namely: (1) homepage; (2) page; (3) quiz; (4) media; (5) setting; and (6) users. This website can be used to carry out assessments that measure students' character development, such as their ability to listen empathetically or communicate honestly through quizzes.